Co-Teaching Level of Regular Teachers and Special Supervisory Teachers in Elementary Schools Providing Inclusive Education in Padang City - Cindy Rahmi Aulia; Hermanto Hermanto (FKIP - Universitas Riau, 2026)
Co-teaching has become a central instructional approach in inclusive education, requiring strong collaboration between general education teachers and special education teachers. This study aimed to evaluate the level of co-teaching implementation in inclusive elementary schools in Padang and to identify the discrepancy between actual practices and the ideal theoretical model. Using a quantitative descriptive design supported by a discrepancy evaluation model, data were collected from seventy-two teachers through a validated and reliable questionnaire measuring five core components of co-teaching. The results indicate that co-teaching is generally implemented at an effective level, with teachers demonstrating positive collaborative interactions and functional shared instructional practices. Cooperative Processes emerged as the strongest component, while Shared Goals, Parity, and Distributed Leadership showed lower levels of development, revealing structural aspects that require improvement. A discrepancy test further confirmed that actual implementation has not fully reached the ideal standard. The study concludes that although co-teaching is progressing well, targeted efforts are needed to strengthen planning structures and collaborative leadership. Future research is recommended to incorporate qualitative observations and investigate the impact of co-teaching quality on student outcomes.